2020
DOI: 10.1002/aws2.1186
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for large building water quality after extended stagnation

Abstract: The unprecedented number of building closures related to the coronavirus disease (COVID‐19) pandemic is concerning because water stagnation will occur in many buildings that do not have water management plans in place. Stagnant water can have chemical and microbiological contaminants that pose potential health risks to occupants. Health officials, building owners, utilities, and other entities are rapidly developing guidance to address this issue, but the scope, applicability, and details included in the guida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 92 publications
(107 citation statements)
references
References 70 publications
4
87
0
Order By: Relevance
“…Another field study identified their most frequently Legionella positive sites as being located at the end of the distribution system and having the highest turbidity, iron, TOC, and water age, as well as the lowest flow [ 247 ]. The association between OPs and stagnation has created interest in strategies to reduce building water stagnation effects such as removing dead-legs, flushing, maintaining the hot water system, and shock disinfection [ 248 , 249 , 250 , 251 ]. The effectiveness of these strategies should be evaluated within the context of the specific pipe materials that are present.…”
Section: Influence Of Plumbing System Design Configuration and Opmentioning
confidence: 99%
“…Another field study identified their most frequently Legionella positive sites as being located at the end of the distribution system and having the highest turbidity, iron, TOC, and water age, as well as the lowest flow [ 247 ]. The association between OPs and stagnation has created interest in strategies to reduce building water stagnation effects such as removing dead-legs, flushing, maintaining the hot water system, and shock disinfection [ 248 , 249 , 250 , 251 ]. The effectiveness of these strategies should be evaluated within the context of the specific pipe materials that are present.…”
Section: Influence Of Plumbing System Design Configuration and Opmentioning
confidence: 99%
“…Building inactivity results in stagnant water in the premise plumbing that can adversely affect water quality, including the loss of residual chlorine, growth of bacteria, and release of harmful metals like lead. 1-4 Temporarily idle buildings is not a new issue (e.g., during the annual summer recess of schools). Yet, there are gaps in the peer-reviewed literature regarding microbiological water quality changes during such closures and the corresponding risks.…”
Section: Introductionmentioning
confidence: 99%
“…Another potential secondary risk comes from the stagnant water in reopening buildings after extended stagnation during the pandemic. Stagnant water can have chemical and microbiological contaminants that pose potential health risks to occupants [80] . In particular, water stagnation in buildings may lead to Legionella growth, but study on the relationship between Legionnaires' disease cases and COVID-19 lockdowns is still limited [81] .…”
Section: State Of the Knowledge And Research Needsmentioning
confidence: 99%